DEVELOPMENT OF TECHNOLOGY FOR DOUGH-BASED NATIONAL DISHES WITH INCREASED BIOLOGICAL VALUE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Increasing the biological value of dough-based national dishes is an important intersection in the field of food science, nutrition and cultural heritage preservation. This article studies innovative technologies aimed at eliminating the widespread micronutrient deficiency in Central Asia by enriching national dishes of Uzbekistan, such as bread, samsa and manty with microelements and bioactive substances, while preserving the sensory and cultural properties of dishes.